2014
DOI: 10.1016/j.jval.2014.08.2310
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Minimization Analysis of Trastuzumab Intravenous Versus Trastuzumab Subcutaneous for the Treatment of Patients With HER2+ Early Breast Cancer And Metastatic Breast Cancer in Greece

Abstract: Objectives: Metastatic melanoma has a poor prognosis with 10 year survival being < 5%. Standard therapy is the effective but costly Ipilimumab. An emerging 1st line treatment is Tumor Infiltrating Lymphocytes (TIL), with response rates > 50% and expected survival rates of 25%-42% versus 45% (1yr) and 23,5% (2yr) for Ipilimumab. TIL is highly personalized, however complex and requests substantial upfront investments from the hospital in expensive lab-equipment, staff expertise and training, as well as extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…[5] A time-and-motion study within the PrefHer study demonstrated a mean time saving of 55-57 min of patient chair time and 13-17 min of active healthcare professional time per session with H SC compared with H IV, [6] and several countries have reported estimated increased hospital capacity and/or costsavings with H SC. [7][8][9][10][11][12][13][14][15][16][17] These data support a transition to SC delivery.…”
Section: Introductionmentioning
confidence: 82%
“…[5] A time-and-motion study within the PrefHer study demonstrated a mean time saving of 55-57 min of patient chair time and 13-17 min of active healthcare professional time per session with H SC compared with H IV, [6] and several countries have reported estimated increased hospital capacity and/or costsavings with H SC. [7][8][9][10][11][12][13][14][15][16][17] These data support a transition to SC delivery.…”
Section: Introductionmentioning
confidence: 82%
“…Although we did not perform a specific cost analysis of the different treatment groups, a previous study has indicated that the cost of treatment with subcutaneous trastuzumab is lower than that with intravenous trastuzumab in the management of patients with early and metastatic breast cancer overexpressing HER2. 10 Hence, the substitution of the intravenous with subcutaneous formulation can produce valuable savings for the Greek health care system, especially in the current economic environment where hospitals’ pharmaceutical budget has significantly been reduced. 10 Furthermore, here, we do not provide a correlation of our results on HRQoL with patients’ survival parameters, as this study has a short time of follow-up and not enough events have occurred for such analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 9 In addition to these advantages, the subcutaneous administration requires less preparation and administration expenses, manpower engagement, and day clinic time resulting in reduced health care system burden and costs. 10 The PrefHer study compared sequential subcutaneous trastuzumab for 4 cycles followed by intravenous trastuzumab and vice versa in patients with HER2+ early breast cancer and showed that the subcutaneous administration was both well tolerated and the preferred option between the 2 formulations. 11 …”
Section: Introductionmentioning
confidence: 99%
“…The study estimated that over one year, switching to SC trastuzumab would result in a reduction of pharmacists and nurses workload by 5492 hours and generate cost savings of £271,000 [22]. Similarly, a study from Greece reported mean total cost per year of IV and SC trastuzumab was €24,163 and €23,042 per patient respectively; with the use of SC resulting in savings of €1121 [23]. Finally, a report from the Scottish Medicines Consortium indicated that switching from IV to SC trastuzumab would generate cost savings for the Scottish NHS of £3454 over one year of treatment arising from reductions in medication and time costs of health care professionals [25].…”
Section: Introductionmentioning
confidence: 99%